Reporting basal cell carcinoma: a survey of the attitudes of histopathologists. Issue 11 (1st November 1999) - Milroy, C J; Richman, P I; Wilson, G D; Sanders, R
Abstract : AIMS: To investigate the histopathological reporting of basal cell carcinoma. METHODS: Methods of classification and attitudes to excision margins were ascertained from histopathologists in 130 centres; 82 replies were obtained (63% response rate). RESULTS: 24% of those replying did not use any classification system for basal cell carcinoma. The remainder (76%) used a wide variety of different classification systems. A small number (9%) of those questioned felt reporting on completeness of excision was not important. The majority of histopathologists considered the excision margin was worth reporting but there were differences in methods of processing and reporting biopsies. CONCLUSIONS: There is considerable variation in histopathological reporting of basal cell carcinoma. There is a need for uniformity of histopathological reporting to allow both improved management decisions and comparative audit of this extremely common skin cancer.